2010
DOI: 10.1093/qjmed/hcq076
|View full text |Cite
|
Sign up to set email alerts
|

Long-term histological follow-up of people with coeliac disease in a UK teaching hospital

Abstract: Current guidelines for the timing of repeat biopsy after commencing a gluten free diet are unclear, although 4-6 months has been recommended. This study shows that time to histological recovery is longer than traditionally thought and may need to take into account the patient's age at diagnosis, the initial disease score and the level of compliance with a gluten free diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 23 publications
4
49
2
Order By: Relevance
“…In accord, Rubio-Tapia et al ( 6 ) discovered an association between the severity of the baseline damage and slow histological recovery. Another recent study ( 37 ) showed that patients with less severe atrophy were also more likely to respond to the diet. However, this was the fi rst time a quantitative approach has been used to assess the actual speed (Δ Vh/CrD) of villous recovery and it was observed to be lower in the Atrophy group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In accord, Rubio-Tapia et al ( 6 ) discovered an association between the severity of the baseline damage and slow histological recovery. Another recent study ( 37 ) showed that patients with less severe atrophy were also more likely to respond to the diet. However, this was the fi rst time a quantitative approach has been used to assess the actual speed (Δ Vh/CrD) of villous recovery and it was observed to be lower in the Atrophy group.…”
Section: Discussionmentioning
confidence: 98%
“…Th is slower recovery combined with severe atrophy at diagnosis explains why these patients had not regained normal mucosa during 1 year despite a strict diet. Some studies have indirectly investigated whether the speed of histological recovery is associated with the severity of the baseline damage, but results have been controversial ( 5,6,9,15,37,38 ). Th is might be explained by diff erences in dietary adherence and by the use of inexact grouped classifi cations (e.g., Marsh) in histology ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, neither symptoms72 150 151 156 158160 nor serology149 is reliable to predict small intestinal damage;149 assessing mucosal healing by biopsy is the key. Serum antibodies have poor sensitivity for persistent villous atrophy, especially 1 year or more after diagnosis and institution of a GFD.…”
Section: Follow-upmentioning
confidence: 99%
“…This condition is usually resistant to treatment and often progresses to an overt intestinal lymphoma and premature death. [6][7][8][9][10] Although up to 79% of long-term treated coeliac disease patients evidence persistent small-bowel mucosal atrophy, [11][12][13][14][15][16][17] genuine RCD is considered to be rare, probably presenting in 1.5-10% of diagnosed coeliac disease patients. 4,13,[18][19][20][21] Nevertheless, the relevant literature is sparse and limited to small case series from tertiary centres.…”
Section: Introductionmentioning
confidence: 99%